1992
DOI: 10.1099/0022-1317-73-6-1429
|View full text |Cite
|
Sign up to set email alerts
|

Antipeptide antisera define neutralizing epitopes on the adenovirus hexon

Abstract: The adenovirus (Ad) hexon contains both group-and type-specific antigenic determinants. To identify the latter, peptides were synthesized corresponding to residues 281 to 292 from loop 1 and 441 to 455 from loop 2 of the Ad2 hexon. These sequences display typespecific variation and have been shown by X-ray crystallography to be present on the surface of the virion. Antisera raised against the peptides bound both peptide and the native hexon in ELISA, and blocked virus infectivity, as determined by immunofluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
70
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(74 citation statements)
references
References 26 publications
4
70
0
Order By: Relevance
“…The present studies extend prior reports that have demonstrated potent neutralizing activity of hexon-specific Abs in vitro (18,19,32). Previous studies have also shown that chimeric rAd5 vectors containing the Ad2, Ad6, or Ad12 hexon genes were able to evade a substantial fraction of anti-Ad5 immunity in rodents (20 -22), although these studies did not differentiate between the contributions of hexon-specific humoral and cellular immunity.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The present studies extend prior reports that have demonstrated potent neutralizing activity of hexon-specific Abs in vitro (18,19,32). Previous studies have also shown that chimeric rAd5 vectors containing the Ad2, Ad6, or Ad12 hexon genes were able to evade a substantial fraction of anti-Ad5 immunity in rodents (20 -22), although these studies did not differentiate between the contributions of hexon-specific humoral and cellular immunity.…”
Section: Discussionsupporting
confidence: 78%
“…A total of 240 hexon capsomeres forms the majority of the capsid structure, whereas 12 vertex capsomeres consist of the fiber attachment proteins and their penton bases. Hexonspecific Abs have been shown by several laboratories to exert significant neutralizing activity in vitro (18,19). Moreover, studies in rodents using hexon-chimeric viruses have suggested that hexon-specific immune responses also contribute substantially to anti-Ad5 immunity in vivo (20 -22).…”
Section: Neutralizing Antibodies To Adenovirus Serotype 5 Vaccine Vecmentioning
confidence: 99%
“…Although the mechanism by which antibodies neutralize adenoviruses is unclear, some neutralizing antibodies do not prevent virus entry into cells and thus may act by inhibiting postentry events (34,37,39,40). It has been proposed that an acidic cluster in the subgroup C adenoviruses may interact with histone-H1 during capsid disassembly at the nuclear pore complex (35); it has also been suggested that this acidic cluster may contribute to conformational changes in the capsid that occur after endosomal acidification (36,39).…”
Section: Discussionmentioning
confidence: 99%
“…1A). Adenovirus-neutralizing antibodies can be raised against any of the major capsid proteins (9,22,34,36,37,40). However, experiments with chimeric viruses-in which capsid components of one serotype were replaced by those of another serotypesuggest that hexon is the predominant target of serotype-specific neutralizing antibodies (10,22,23,32,44).…”
mentioning
confidence: 99%
“…Three regions that are likely to contain neutralization determinants showed mutations: the L1 region encoding polypeptide IIIa, associated with hexon units that surround the penton, L3 region encoding polypeptides forming hexon and L5 region that encodes polypeptides forming the fiber. Toogood et al (1992) recognize that although several different epitopes in polypeptides forming hexon, fiber and penton base are involved in neutralization tests, some are more effective than others. Using monoclonal antibodies to Ad5 it was described 19 different epitopes in hexon, being one of this common to all adenovirus serotypes, another found also in Ad1 and Ad6 but not in Ad2 (Russell et al 1981).…”
Section: Discussionmentioning
confidence: 99%